Please wait...
1800-212-7858 (Toll Free)
9:00am - 8:00pm IST all days

or

Thanks, You will receive a call shortly.
Customer Support

You are very important to us

For any content/service related issues please contact on this toll free number

022-62211530

Mon to Sat - 11 AM to 8 PM

to prove

Asked by 20th February 2009, 5:27 PM
Answered by Expert
Answer:

a x b = b x c not equal to 0

post multiply by a

ax (a x b ) = a x (b x c)

a(a.b) - b (a.a) = b (a.c) - c (a.b)......(1)

now post multiply with c

c x(a x b ) = c x (b x c)

a(b.c) - b (a.c ) = b (c.c) - c (c.b) .....(2)

add (1) and (2)

(a+c) (a.b +b.c) = b ( a.a+a.c+c.c+a.c)

so a+ c = mb

where m = ( a.a+a.c+c.c+a.c) / (a.b +b.c)

hence proved

Answered by Expert 20th February 2009, 10:39 PM
Rate this answer
  • 1
  • 2
  • 3
  • 4
  • 5
  • 6
  • 7
  • 8
  • 9
  • 10

You have rated this answer /10

Your answer has been posted successfully!

Free related questions

17th June 2016, 10:14 AM
17th June 2016, 12:17 PM
17th June 2016, 11:04 AM
17th June 2016, 11:47 AM
23rd June 2016, 5:44 PM

Chat with us on WhatsApp